Mechanisms of hemispheric lateralization: A replication study. (September 2017) - Wende, Kim C.; Thiel, Catherine; Sommer, Jens; Paulus, Frieder M.; Krach, Sören; Jansen, Andreas
Abstract: It has been shown, using functional magnetic resonance imaging (fMRI), that hemispheric lateralization of brain activity depends on the requirements of the cognitive task performed during the processing of a sensory stimulus rather than on the intrinsic characteristics of that stimulus [Stephan et al., 2003, Science 301 (5631): 384–6]. Task-dependent increase in the coupling of the anterior cingulate cortex (ACC), a region involved in cognitive control, and brain areas in the left prefrontal and right parietal cortex, respectively, regions involved in task execution, was proposed as the mechanism underlying this task-dependency of hemispheric lateralization. The aim of the present study was two-fold: First, we aimed for a conceptual replication of these findings in an independent sample of subjects. Second, we investigated the test–retest reliability of the imaging paradigm to assess whether the task can be used to capture reliable measures of inter-individual differences in hemispheric lateralization. We were able to confirm previous findings showing that hemispheric lateralization depends on the nature of the cognitive task rather than on the nature of the processed stimuli. The task-related brain activation patterns were highly reliable across sessions (as indicated by intra-class correlation coefficients – ICCs, ≥.51). We could, however, not replicate previous results proposing task-dependent changes in the coupling between ACC and brain regions for task execution as the mechanism underlying hemispheric lateralization. This re-opens the question which mechanisms could determine the task-dependent functional asymmetries that were observed previously and replicated in this study.